The Relationship between the Dimensions of Quality of Health Services with Inpatient Patient Satisfaction at Mother and Child Hospital X Semarang City - Achmad Yoga Setyo Utomo; Bagoes Widjanarko; Zahroh Shaluhiyah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
Patient satisfaction greatly depends on the quality of hospital services since it can guarantee that patients receive efficient, secure, and uniform care. This study's goal was to ascertain how the mother and child hospital X in Semarang City's inpatient patient satisfaction levels relate to various aspects of health care quality. This study uses a cross-sectional research design, a quantitative technique, and analytical analysis. There were 61 inpatients in this study's group. Total sampling was the method employed for sampling in this investigation. There were 61 patients in the study's sample. The four aspects of service quality availability, responsiveness, convenience, and timeliness are the independent variables in this study, and patient satisfaction is the dependent variable. Data collection using questionnaires. Bivariate data analysis was performed using the Chi-square test which was analyzed using the help of SPSS software version 26. There is no relationship between the availability dimension and patient satisfaction (p-value=0.000), there is no relationship between the responsiveness dimension and patient satisfaction (p-value=0.000), there is no relationship between the convenience dimension and patient satisfaction (p-value=0.008) and there is no relationship between the timeliness dimension (p-value=0.016) at the mother and child hospital X Semarang City. The dominant variable that affects patient satisfaction is the perception of the availability dimension (p-value=0.000; OR=20.789; 95% CI =4.083-107.031). It is hoped that hospital management in its services is expected by doctors to be able to provide a sense of empathy to respond to complaints from patients, and doctors can inform the officers on duty regarding visite hours so that patients feel better served. And the midwife or nurse should make a small information board containing information related to the schedule of the officers' work hours. Keywords: Dimensions, Quality of service, Patient satisfaction, Hospital